Syntactic development, its input and output - Ninio, Anat. (Oxford : Oxford University Press, 2011)
This text places the syntactic learning process under close scrutiny. Its focus is on the characteristics of linguistic input and the resultant output, which, it suggests, do not follow the orderly uniform processes assumed by some versions of formalistic linguistic theory.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Language acquisition; Grammar, Comparative and general -- Syntax